Estimation of genetic and non-genetic factors for test-day milk yield in Mehsana buffaloes - Parmar, Girish A; Gupta, Jay Prakash; Chaudhari, Jagdish D; Prajapati, Bhavesh M; Panchasara, Harshadkumar H; Ankuya, Kanubhai J; Chauhan, Hareshbhai D; Patel, P A (Indian Journal of Dairy Science, 2017)
The data pertaining to various test day yields in Mehsana buffaloes (12524 lactation production records of 7870 buffaloes) were collected from Dudhsagar Research and Development Association (DURDA), Dudhsagar Dairy, Mehsana for the period from 1986 to 2013. The analysis of variance revealed highly significant (P≤0.01) effect of parity of lactation, season of calving, clusters, period of calving and age at first calving group had on all test-days yields in Mehsana buffaloes. The h2 estimates for all test day yields were low but highly significant. The heritability and repeatability estimates for test-day milk yields ranged from 0.07±0.01 in TDY1 to 0.17±0.02 in TDY6 and 0.008±0.12 for TDY11 to 0.41±0.06 for TDY6, respectively, in the present study. All repeatability estimates of the TDYs were significantly different from zero, except TDY11. The repeatability estimates for test-day milk yields observed higher in period of mid lactation. The rg between various TDYs of overall lactation ranged from 0.49±0.89 / 0.49±0.97 (between TDY2 and TDY10 / between TDY2 and TDY11) to 0.99±0.13 / 0.99±0.49 (between TDY4 and TDY5 / between TDY7 and TDY8). The rp between TDY6 and TDY11, TDY7 and TDY11, TDY8 and TDY11 were highly significant (P≤0.01), however, rg between TDY5 and TDY11 was significant (P≤0.05), rest of all TDYs were non-significant.